Antarctic Cryptoendolithic Fungal Communities Are Highly Adapted and Dominated by Lecanoromycetes and Dothideomycetes - Coleine, Claudia; Stajich, Jason; Zucconi, Laura; Onofri, Silvano; Nuttapon Pombubpa; Egidi, Eleonora; Franks, Ashley; Buzzini, Pietro; Selbmann, Laura (Zenodo, 2018)
This is the final paper "Antarctic Cryptoendolithic Fungal Communities Are Highly Adapted and Dominated by Lecanoromycetes and Dothideomycetes" published in Frontiers in Microbiology, Volume 9, 2018,1392 https://www.frontiersin.org/articles/10.3389/fmicb.2018.01392/full : Funded by the Italian National Program for Antarctic Researches (PNRA)